Drug-drug interactions with direct oral anticoagulants for the prevention of ischemic stroke and embolism in atrial fibrillation: a narrative review of adverse events. Issue 4 (3rd April 2023) - Stöllberger, Claudia; Schneider, Birke; Finsterer, Josef
ABSTRACT: Introduction: In randomized trials, direct oral anticoagulants (DOAC) were non-inferior to the vitamin-K-antagonist (VKA) warfarin in preventing stroke/embolism in patients with atrial fibrillation (AF). DOAC are substrates for P-glycoprotein (P-gp), CYP3A4 and CYP2C9. The activity of these enzymes is modulated by several drugs which might induce pharmacokinetic drug-drug interactions (DDI). Drugs affecting platelet function have the potential for pharmacodynamic DDI of DOAC. Areas covered: The literature was searched for: 'dabigatran, ' 'rivaroxaban, ' 'edoxaban, ' or 'apixaban' and drugs affecting platelet function, CYP3A4-, CYP2C9- or P-gp-activity. Reports about bleeding and embolic events attributed to DDI with DOAC in AF-patients were found for 43 of 171 drugs with interacting potential (25%), most frequently with antiplatelet and nonsteroidal anti-inflammatory drugs. Whereas a co-medication of platelet-affecting drugs is invariably reported to increase the bleeding risk, the findings regarding P-gp-, CYP3A4- and CYP2C9- activity-affecting drugs are ambiguous. Expert opinion: Tests for plasma DOAC-levels and information about DDI of DOAC should be widely available and user-friendly. If advantages and disadvantages of DOAC and VKA can be investigated exhaustively, individualized anticoagulant therapy can be offered to patients, considering co-medication, comorbidities, genetic and geographic factors and the health care system.